The relationships between hamstring flexibility, lumbar flexion, and low back pain in rowers - Stutchfield, B. M.; Coleman, S. (European Journal of Sport Science, 2002)
In this study, we examined the relationships between low back pain, hamstring flexibility, and lumbar flexion in rowers. Twenty-six male university rowers participated. Hamstring flexibility was assessed using an adjusted straight leg raise technique, and lumbar flexion was assessed via a distraction of skin marks protocol while long sitting. A questionnaire ascertained rowing details and low back pain characteristics. Low back pain was highly prevalent. No association was observed between low back pain and hamstring flexibility, or between hamstring flexibility and lumbar flexion. Sufferers of low back pain showed reduced lumbar flexion (P=0.03; 95% confidence interval = - 3.7 to -0.2). Results obtained using the adjusted straight leg raise technique suggested that low back pain was not associated with hamstring inflexibility, which suggests that increasing hamstring flexibility for rehabilitation or prevention of low back pain in rowers might not be necessary.